2018
DOI: 10.1186/s13567-018-0534-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanisms of resistance to Teladorsagia circumcincta infection in sheep through transcriptome analysis of abomasal mucosa and abomasal lymph nodes

Abstract: The present study exploited the RNA-seq technology to analyze the transcriptome of target tissues affected by the Teladorsagia circumcincta infection in two groups of adult ewes showing different statuses against gastrointestinal nematode (GIN) infection with the aim of identifying genes linked to GIN infection resistance in sheep. For this, based on the accumulated faecal egg count of 18 adult Churra ewes subjected to a first experimental infection with T. circumcincta, six ewes were classified as resistant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 52 publications
0
31
0
1
Order By: Relevance
“…Furthermore, the correlations between RNA-Seq and the mRNA expression level from qRT-PCR were relatively high. Until now, RNA-Seq has been successfully applied to transcriptome analysis in the sheep [1114]. In the current study, by comparative analysis and imperative validation, 622 differentially expressed genes were identified by pairwise comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the correlations between RNA-Seq and the mRNA expression level from qRT-PCR were relatively high. Until now, RNA-Seq has been successfully applied to transcriptome analysis in the sheep [1114]. In the current study, by comparative analysis and imperative validation, 622 differentially expressed genes were identified by pairwise comparison.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high-throughput sequencing technologies, especially RNA-Seq has been widely utilized to explore potential candidate genes which affect important economic traits in animals. In sheep, many studies of RNA-Seq have been conducted using muscle [11], adipose tissues [12], ovarian tissues [13], and abomasal mucosal [14]. However, limited studies on the transcriptome of liver tissues have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…One major problem for goats and sheep genomic analysis was that the functional analysis was not available with goats or sheep as reference species due to the lack of data for C. hircus and Ovis aries in functional analysis programs. Therefore, almost all previous publications in goats and sheep genomic filled used human [27][28][29] or bovine [30] genome as reference for functional analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have exploited the information derived from an RNA‐Seq experiment with the aim of identifying potential causal mutations related to GIN resistance in sheep. For that, after the general characterisation of the transcriptomic variants of the abomasal lymph node of 12 adult Churra sheep after an experimental infection with Teladorsagia circumcincta (Chitneedi et al ), we performed a detailed analysis of the variants identified in critical genome regions, related to QTL and candidate genes for parasite resistance. Hence, we provide here a list of potential functional variants within immune‐related genes that could be considered, e.g.…”
Section: Introductionmentioning
confidence: 99%